1957
DOI: 10.1017/s0021859600032913
|View full text |Cite
|
Sign up to set email alerts
|

A study of the lactation and growth of hill sheep in their native environment and under lowland conditions

Abstract: 1. A method is described suitable for the estimation of the milk yield of sheep under natural grazing conditions.2. The yields obtained from Welsh Mountain sheep in two environments are shown.3. A close but diminishing relationship is shown to exist between the milk yield of the ewe and the growth of the lamb. Evidence is given of the effect of milk yield at later stages.4. The estimation of the ewe's milk yield from the weight of the young lamb is discussed. These estimates are used in conjunction with actual… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
42
1
2

Year Published

1962
1962
1990
1990

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 59 publications
(52 citation statements)
references
References 19 publications
7
42
1
2
Order By: Relevance
“…Milk yields were estimated by a modification of the method described by Owen (1957), and involved the use of udder covers to prevent the lambs from gaining access to them between recorded sucklings. These took place at 3-hourly intervals over a 12 hr.…”
Section: Estimation Of Milk Yieldmentioning
confidence: 99%
See 1 more Smart Citation
“…Milk yields were estimated by a modification of the method described by Owen (1957), and involved the use of udder covers to prevent the lambs from gaining access to them between recorded sucklings. These took place at 3-hourly intervals over a 12 hr.…”
Section: Estimation Of Milk Yieldmentioning
confidence: 99%
“…That considerable individual variation in productive performance exists within a group of ewes grazing on the same pasture is well known (see Owen, 1957). The factors contributing to these variations have not been adequately investigated and only a few studies, such as those of Arnold (1960) and Cook, Mattox & Harris (1961), have been made on the food intake of grazing ewes.…”
mentioning
confidence: 99%
“…Milk production of the ewe has been reported by some workers to be associated with body weight of the ewe (Burris and Baugus, 1955;Owen, 1957). Ray and Smith (1966) reported results based on 962 birth and 805 weaning weights.…”
mentioning
confidence: 99%
“…Both Barnicoat et al (1956a, b) and Owen (1957) in their extensive studies of milk production in sheep did not find consistent association between age of ewes and amount of milk secreted.…”
Section: Age Of Dammentioning
confidence: 90%
“…Milk yield of the ewe seems to he the most important factor influenc ing the growth of young lambs, especially in the first few weeks when the lamb is wholly dependent on milk (Owen, 1957/ and Donald, I962), Montanaro in 19^9 (as reported by Owen, 1957} found that milk production increased in succeeding lactations to reach the maximum in the fifth and subseq.uently declined. Both Barnicoat et al (1956a, b) and Owen (1957) in their extensive studies of milk production in sheep did not find consistent association between age of ewes and amount of milk secreted.…”
Section: Age Of Dammentioning
confidence: 95%